RADT-18. LONG-TERM FOLLOW-UP OF PATIENTS TREATED WITH GAMMA KNIFE® STEREOTACTIC RADIOSURGERY (GK-SRS) FOR VESTIBULAR SCHWANNOMA (VS). (9th November 2020) - Retzlaff, Amber; Straza, Michael; Bovi, Joseph; Siker, Malika; Friedland, David; Harris, Michael; Zwagerman, Nathan; Albano, Katherine; Wu, Ruizhe; Banerjee, Anjishnu; Schultz, Christopher
Abstract: PURPOSE: GK-SRS is an accepted definitive treatment option for appropriately selected patients with VS. To assess long-term outcomes in VS patients treated with GK-SRS, we retrospectively evaluated all patients treated at our institution from 2007-2019. METHODS: For VS patients treated with GK-SRS from 2007-2019, clinical data (symptoms, physical exams, audiograms, and imaging) was collected via retrospective chart review at pre-treatment and standard follow-up intervals (6 weeks, 6 months, 12 months, then annually). Descriptive analyses, including the proportions of patients in different grades of clinical parameters, are reported. For each clinical parameter, only patients with both pre- and post-treatment data were included in the evaluation set used for analysis. RESULTS: Of 177 patients identified, 46 were excluded from the evaluable set (age < 18 years, prior resection, NF-2, or no follow-up). Among the remaining 131, median follow-up was 42 months (6 weeks to 11 years), and 36.6% completed 5+ years of follow-up. At time of treatment, median age was 61 years, and median Karnofsky Performance Score was 90. 58.0% of lesions were left-sided, and 42.0% were right-sided. The majority were Koos grade II (37.4%) or III (38.2%); the remainder were grade I (13.0%) or IV (11.5%). Pre-treatment central necrosis and ventriculomegaly were present in 39.7% and 4.6%, respectively. Following treatment, audiogram analysis with Gardner-Robertson Hearing Score demonstrated no change in 48.9%, some level of decline in 47.8%, and improvement in 3.3% at last follow-up. 97.7% had House-Brackmann scores of I at diagnosis; the remainder were House-Brackmann II. House-Brackmann scores remained unchanged at last follow-up for 96.9%, improved for 1.6%, and worsened for 1.6%. Salvage therapy in the form of surgery (n=5) or repeat GK-SRS (n=2) was necessary in 5.3% (n=6 for progression; n=1 for trigeminal symptoms). CONCLUSION: Long-term follow-up demonstrates that GK-SRS remains a well-tolerated, primary definitive treatment for VS.